Linear parameter varying control for XV-15 tiltrotor vehicle during transition - Yang, H.; Morales, R.M. (My University, 2021)
This manuscript applies Linear-Parameter-Varying control methods to a validated XV-15 tilt rotor vehicle, aiming to develop the flight control system specifically for the transition period. The proposed control law uses self-scheduling H? design synthesis, which not only guarantees the closed-loop stability over the entire parameter space, but also ensures a prescribed level of performance. Simulation results show that the controller can offer very good performance in terms of reference tracking and disturbance rejection, indicating that the pilot’s workload can be reduced significantly